Production of CFTR-ΔF508 Rabbits - Yang, Dongshan; Liang, Xiubin; Pallas, Brooke; Hoenerhoff, Mark; Ren, Zhuoying; Han, Renzhi; Zhang, Jifeng; Chen, Y. Eugene; Jin, Jian-Ping; Sun, Fei; Xu, Jie (Frontiers in Genetics, 2021)
Cystic Fibrosis (CF) is a lethal autosomal recessive disease caused by mutations in the gene encoding the cystic fibrosis transmembrane conductance regulator (CFTR). The most common mutation is the deletion of phenylalanine residue at position 508 (∆F508). Here we report the production of CFTR-∆F508 rabbits by CRISPR/Cas9 mediated gene editing. After microinjection and embryo transfer, 77 kits were born, of which 5 carried the ∆F508 mutation. To confirm the germline transmission, 1 male ∆F508 founder was bred with 2 wild-type females and produced 16 F1 generation kits, of which 6 are heterozygous ∆F508/WT animals. Our work adds CFTR-∆F508 rabbits to the toolbox of CF animal models for biomedical research.